Abusive Supervision and Career Adaptability: The Role of Self-Efficacy and Coworker Support. Issue 4 (8th August 2021) - Rasheed, Muhammad Imran; Weng, Qingxiong; Umrani, Waheed Ali; Moin, Muhammad Farrukh
ABSTRACT: Recent literature on abusive supervision has suggested its negative impact on a number of work outcomes. However, we still have little knowledge about the impact of destructive leadership on employee career outcomes. Drawing on social cognitive theory (SCT), we propose that abusive supervision challenges employee career adaptability by damaging career self-efficacy beliefs in the workplace. Three-wave data collected from 287 employees working in different organizations situated in China has shown that abusive supervision is negatively related to employee career adaptability through career self-efficacy. Moreover, coworker support was found to buffer the association between abusive supervision and career adaptability such that the relationships are weaker at higher levels of coworker support. Implications for researchers and practitioners and research directions for the future are discussed.